Examination of Lexical Derivation in Terminology Associated with Creative Tourism - Ni Luh Supartini; I Nengah Sudipa; I Wayan Pastika; I Wayan Simpen (International Journal of English and Applied Linguistics (IJEAL), 2024)
This article discusses the analysis of morphological aspects, particularly word formation, utilized in tourism terminology. The author discovered numerous new terms emerging in the realm of creative tourism, particularly tailored for tourists. This evolution is spurred by the proliferation of diverse forms of tourism, arising from the desire to break free from the monotony of daily routines. The study revealed that these novel terms can be classified into blending and compounding types. These formations are increasingly ingrained in the minds of tourists and the local community, making them commonplace in the lexicon of creative tourism. This linguistic variation is heavily influenced by the evolving demands of tourists. Basically, the new word formations consist of combining two words to signify novel meanings aligned with the requirements of contemporary creative tourism.